WP1-14 A systematic review to evaluate different management strategies for incidental intracranial meningiomas. Issue 3 (14th February 2019) - Mohan, M; Islim, A; Moon, RDC; Srikandarajah, N; Brodbelt, AR; Mills, SJ; Jenkinson, MD
Abstract : Objectives: Evaluate the outcomes of differing management strategies for incidental intracranial meningiomas. Design: Systematic review. Subjects: Studies with ≥10 patients≥16 years of age diagnosed radiologically with an incidental intracranial meningioma. Methods: PRISMA compliant methods were used to scan 6 databases up to September 2017. PROSPERO ID: CRD42017077928. Results: Twenty retrospective studies (n=2130 patients) were included. Initial management strategies at diagnosis were: 27% (n=560) surgery, 22% (n=450) SRS and 51% (n=1040) active monitroing with a mean follow-up of 49.5 months (SD=29.3). 21% (n=220) of patients in the active monitoring cohort eventually had or were recommended an intervention due to: radiological progression (n=153), development of symptoms (n=66) and patient preference (n=1). Mean time-to-intervention was 24.8 months (SD=18.2). 94% (n=207) of interventions were within 5 years. The definition of 'growth' and the radiological surveillance regimens varied widely. Morbidity rates following surgery and SRS, accounting for cross over, were 15% and 22% respectively. Surgery revealed benign histology in 94% of the cases. Quality of life is improperly examined. Conclusions: The management of patients with incidental intracranial meningiomas varies widely. Most patients who develop clinical or radiological progression will do so within 5 years of diagnosis. Intervention at diagnosis may result in unnecessary overtreatment. Prospective data is needed to develop a risk calculator for managing incidental meningioma.